Factors Affecting Students’ Acceptance of Gamified Learning (SAGL) - Randle, Oluwarotimi A. (Studies in Learning and Teaching, 2024)
Gamification is commonly used for improving student learning experiences. The purpose of this paper is to understand the factors that influence the acceptance of gamification in learning. The paper employs a meta-analysis approach to identify the factors that affect students’ acceptance of gamified learning. The benefit of meta-analysis is its ability to synthesize and utilize the results obtained from various primary research papers to discover the critical factors that influence the acceptance of game design elements in online courses. The PRISMA protocol was used to analyze the meta-analysis. While much research has been done on gamified learning, there is a lack of meta-analysis research on the acceptance of gamified learning elements. The results of the meta-analysis indicated that performance expectancy, student satisfaction, and social interaction are the critical factors influencing the acceptance of gamified learning. These results are beneficial because they not only focus on learning but also provide an opportunity for industry experts to be aware of the critical factors that influence the acceptance of gamified learning. This paper’s novelty lies in its analysis of statistical heterogeneity, effect size, and publication bias across research that employed various statistical techniques.